Ecology and Demography of Free-Roaming Domestic Dogs in Rural Villages near Serengeti National Park in Tanzania. - Anna M Czupryna; Joel S Brown; Machunde A Bigambo; Christopher J Whelan; Supriya D Mehta; Rachel M Santymire; Felix J Lankester; Lisa J Faust (PLoS ONE, 2016)
Free-roaming dogs (Canis lupus familiaris) are of public health and conservation concern because of their potential to transmit diseases, such as rabies, to both people and wildlife. Understanding domestic dog population dynamics and how they could potentially be impacted by interventions, such as rabies vaccination, is vital for such disease control efforts. For four years, we measured demographic data on 2,649 free-roaming domestic dogs in four rural villages in Tanzania: two villages with and two without a rabies vaccination campaign. We examined the effects of body condition, sex, age and village on survivorship and reproduction. Furthermore, we compared sources of mortality among villages. We found that adult dogs (>12mos) had higher survival than puppies in all villages. We observed a male-biased sex ratio across all age classes. Overall survival in one non-vaccination village was lower than in the other three villages, all of which had similar survival probabilities. In all villages, dogs in poor body condition had lower survival than dogs in ideal body condition. Sickness and spotted hyena (Crocuta crocuta) predation were the two main causes of dog death. Within vaccination villages, vaccinated dogs had higher survivorship than unvaccinated dogs. Dog population growth, however, was similar in all the villages suggesting village characteristics and ownership practices likely have a greater impact on overall dog population dynamics than vaccination. Free-roaming domestic dogs in rural communities exist in the context of their human owners as well as the surrounding wildlife. Our results did not reveal a clear effect of vaccination programs on domestic dog population dynamics. An investigation of the role of dogs and their care within these communities could provide additional insight for planning and implementing rabies control measures such as mass dog vaccination.